5X+X=6X+3

Simple and best practice solution for 5X+X=6X+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5X+X=6X+3 equation:


Simplifying
5X + X = 6X + 3

Combine like terms: 5X + X = 6X
6X = 6X + 3

Reorder the terms:
6X = 3 + 6X

Add '-6X' to each side of the equation.
6X + -6X = 3 + 6X + -6X

Combine like terms: 6X + -6X = 0
0 = 3 + 6X + -6X

Combine like terms: 6X + -6X = 0
0 = 3 + 0
0 = 3

Solving
0 = 3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 2x-y+6z=20 | | x+7-2=3x | | 4-6x+8=1-5x-4 | | 8=3h+5 | | (0-k)(1-k)=0 | | 2x^2+10+52=0 | | (X+3)+2(X-4)=5(X+3) | | (0-k)(0-k)=0 | | X+2x+2x-30=140 | | 9(x+8)+12=8(x+18)+10 | | Y=-3x*2 | | Y=4x^2+3x | | 2=2x-6x+3x+9 | | 360-65-x=44 | | q=40+-0.5p | | 3+4(2x+5)=39 | | 48/6= | | x^2+30x-40=0 | | 5x+5=52 | | 4-293x-4=1-(5x+4) | | 0+50*1-60-60*0+10=C | | q=40-0.5p | | -100+82=x | | 4(5x-1)-10x=3 | | -6x-3.4=3x+.2 | | -70-(-58)=x | | x^2+12x+56=0 | | -6x(x+4)-x^2+8-5x= | | 7x^8-38x^6+15x^4=0 | | 5x^4-11x^2+2=0 | | 2+w=-6 | | 5m^4-7m^2-6=0 |

Equations solver categories